Pengaruh Gaya Kepemimpinan Islami, Reward, dan Punishment tarhadap Kinerja Karyawan dengan Motivasi Kerja sebagai Variabel Moderasi pada Karyawan Brownies Cinta Karanganyar - Erisa Nabilah Shintianingsih; Budi Utomo (Jurnal Manajemen Bisnis Syariah, 2024)
This research was conducted to determine the influence of Islamic leadership style, reward and punishment on employee performance with work motivation as a moderating variable for Brownies Cinta Karanganyar employees. The research method used is a quantitative method with a saturated sample technique. Data collection in this research was carried out by distributing questionnaires to Brownies Cinta Karanganyar employees with a population and sample of 50 employees. From the results of the analysis carried out, it was found that (1) Islamic Leadership Style has a positive and significant effect on employee performance. (2) Rewards have a negative and significant effect on employee performance. (3) Punishment has no significant effect on employee performance. (4) Work Motivation is unable to moderate Islamic Leadership Style on Employee Performance. (5) Work motivation is unable to moderate rewards for employee performance. (6) Work Motivation is unable to moderate punishment of employee performance